Prenatal Exposures Are Associated With Worse Neurodevelopmental Outcomes in Infants With Neonatal Opioid Withdrawal Syndrome - Benninger, Kristen L.; Borghese, Teresa; Kovalcik, Jason B.; Moore-Clingenpeel, Melissa; Isler, Cherie; Bonachea, Elizabeth M.; Stark, Ann R.; Patrick, Stephen W.; Maitre, Nathalie L. (Frontiers in Pediatrics, 2020)
Aim: To define a developmental trajectory in infants with neonatal opioid withdrawal syndrome (NOWS) and determine whether impacted developmental domain varies with type of antenatal exposure. Methods: We performed a retrospective cohort study of infants treated pharmacologically for NOWS and assessed using a standardized schedule for follow-up visits. We compared outcomes of the study population to published norms using one-sample t-tests. Multivariable models examined associations with exposures in addition to opioids. Results: In our cohort of 285 infants with 9-12 month testing, 164 (55.7%) were seen at 3-4 months, and 125 (44%) at 15-18 months. The majority (58%) had intrauterine drug exposures in addition to opioids. Neurodevelopmental scores of infants with NOWS at 3-4 and 9-12 months were not different from published norms. Cognitive and language scores at 15-18 months were worse than published norms. Male sex, older maternal age and additional barbiturate or alcohol exposure were associated with worse outcomes. Conclusion: Infants with pharmacologically treated NOWS had development similar to un-exposed infants during the first year but worse cognitive and language scores during the second year. These data support the need for prospective follow-up of large cohorts of infants with NOWS, with systematic assessments and evaluation of contributing factors.